'Superbugs': raising public awareness of antimicrobial resistance through a pop-up science shop. (15th February 2022) - Tyrrell, Jonathan M.; Conlon, Christie S.; Aboklaish, Ali F.; Hatch, Sarah; Smith, Carl; Mathias, Jordan; Thomson, Kathryn; Eberl, Matthias
Abstract : page_1 other 'Superbugs: A Pop-up Science Shop' was a public engagement event in the school summer holidays of 2019, organised by members of Cardiff University's School of Medicine. We transformed an empty retail unit in the centre of Wales's largest shopping centre into an interactive and immersive microbiology experience. We facilitated two-way dialogue to impart positive impact on the awareness of antibiotic resistance, while concurrently evaluating the efficacy of an engagement strategy focused on the utilisation of public spaces to attract public demographics diverse to those who would normally engage with conventional science, technology, engineering and mathematics (STEM) outreach. Over the course of 14 days, we welcomed 6, 566 visitors, with 67 per cent attending as part of the natural footfall of the shopping centre. We created 1, 626 young Antibiotic Resistance Champions, located in over two hundred schools, across many of the most deprived areas in Wales. We imparted a positive page_2 other impact to our stakeholders, with a significant increase in the knowledge and understanding of the subject of antimicrobial resistance (AMR); 91.7 per cent indicated that they had a better understanding after the event. In this article, we discuss the evolution of 'Superbugs' from concept, planning and design, to the logistics of delivering an engagement event of this scale. We focus in particular on the learning outcomes of the project, and on how this will shape the future of our 'Superbugs' project, and engagement events beyond.